The Impact of proposed exercises according to some biomechanical variables in the development of speed return the topspin serve in tennis - Latif , Abdullah (Journal of Physical Education, 2011)
The aims of the study were : - Understanding the values of some biomechanical variables during the performance of the return the top spin serve in tennis to the research sample . - Making proposed exercises to some biomechanical variables For Developing The Speed return the top spin serve in tennis . - Identifying the effect of the suggested exercises For Developing The Speed return the top spin serve in tennis . The Hypothesis Of the Study : - There are significant differences between the pre and post tests for research sample for Developing The Speed return the top spin serve in tennis and in favor of the post tests . The researcher used the experimental method. He used one group with two tests; pre tests and post tests. The subjects were four young elite tennis players from the union tennis branch of the Erbil town , and the final sample numbers (5) players , The researcher used many apparatus and tools , and using (5) cameras for analysis , one fast camera from them . the analysis procedure on return the serve for knowing some biomechanical variables it relates the player and ball . and using many statistics aides (SPSS and Excel) programs to taking Results for display , analysis and discussion . The researcher concluded that : - contributed to the proposed exercises according to some biomechanical variables to increase the speed in return the serve significantly in the post-test for pre-test . Finally the researcher recommended the following : - It’s necessary to take advantage to backhand swing and increase acceleration in forehand swing and hit the ball in maximum height with concentration on feet work . - Linking the force and speed exercises with performance skills exercises , such as counteraction exercises with the performance basic tennis skills .